1977
DOI: 10.2307/1935602
|View full text |Cite
|
Sign up to set email alerts
|

Egg Development, Growth, and Metabolism of Sigara Alternata (Say) (Hemiptera: Corixidae) in Fluctuating Thermal Environments

Abstract: Egg development and growth of Sigara alternata in southeastern Pennsylvania, USA were evaluated in six fluctuating temperature regimes with daily maxima ranging from 12.0° to 21. 5°C. Developmental rate was positively correlated with increased magnitude of the diel temperature pulse. Developmental acceleration was most apparent for environments pulsing beyond 15.0°C for both stages. Oviposition rates were studied at natural temperatures during the initial days of reproduction. Egg deposition was sporadic but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 54 publications
6
47
0
Order By: Relevance
“…Moreover, even if LC was not tested at FT, conductivity did not affect either hatching time of resting eggs or physiological time at completion of life cycle in generation I. This result confirms that natural thermal fluctuation, from day to night and from colder to wormer months, influence developing of invertebrates (Sweeney and Schnack, 1977;Ikeda, 1992;Montagnes and Weisse, 2000;Putnam et al 2010), but an acceleration of growth rate in fluctuating temperatures was observed in Daphnia (Orcutt and Porter, 1983) and rotifers (Halbach, 1973). Moderate thermal fluctuations may be associated with faster growth while retardation of development was described in fluctuating regimes encompassing extreme temperatures (Worner, 1992;Thorp and Wineriter, 1981).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, even if LC was not tested at FT, conductivity did not affect either hatching time of resting eggs or physiological time at completion of life cycle in generation I. This result confirms that natural thermal fluctuation, from day to night and from colder to wormer months, influence developing of invertebrates (Sweeney and Schnack, 1977;Ikeda, 1992;Montagnes and Weisse, 2000;Putnam et al 2010), but an acceleration of growth rate in fluctuating temperatures was observed in Daphnia (Orcutt and Porter, 1983) and rotifers (Halbach, 1973). Moderate thermal fluctuations may be associated with faster growth while retardation of development was described in fluctuating regimes encompassing extreme temperatures (Worner, 1992;Thorp and Wineriter, 1981).…”
Section: Discussionsupporting
confidence: 62%
“…To mimic the natural thermal fluctuations that affect invertebrate development (Hubbs, 1964;Sweeney and Schnack, 1977;Scholnick, 1995), two more microcosms were maintained on the laboratory windowsill from February to May. Throughout the experimental period, in our laboratory (45° latitude N), temperature and photoperiod were similar to the early spring breeding hydroperiod in Lampedusa.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation is possibly caused by preys (food) that are more abundant at locations with increased nutrient concentrations (Maul et al 2004). This is supported by previous studies which demonstrated that Corixidae feed on stream bottom organic matter containing algae, diatoms (Alahmed et al 2009;Cummins 1973;Sweeney & Schnack 1977) and Gerridae feed on detritivores and small arthropods at or near water surface that could be more abundant related to increasing nutrient concentrations (Cummins 1973;Jardine et al 2008;Sih & Watters 2005). Fernandez and Lopez Ruf (2005) reported that Gerridae was found in streams that subjected to agricultural and cattle-rearing activities in La Plata estuary, Argentina.…”
Section: Distribution and Diversity Of Aquatic Insects Communitysupporting
confidence: 70%
“…growth and metabolism under warming; Sweeney & Schanck 1977) or focal species populations (e.g. polewards or altitudinal range shifts; Babaluk et al 2000).…”
Section: Scales Of Study and Levels Of Biological Organizationmentioning
confidence: 99%